Pengembangan Aplikasi Pembelajaran Pemrograman Java yang Atraktif Berbasis Android - Riski Pradana; Bayu Priyambadha; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In the Faculty of Computer Science (FILKOM) Brawijaya University, the survey shows that 76% of 100 FILKOM students are more interested in studying materials other than the basic programming courses. Limitations of material resources obtained and Student Centered Learning methods that used in FILKOM are considered less helpful for students to understand the learning materials. Therefore, it has developed an attractive java programming learning system based on website using gamification method. However, research from Studi Baidu states that users of mobile applications are 97%, greater than browsers that only 76%. Some studies related to gamification also states that the next research direction is from the side of mobility. Based on this data, need to develop Java learning programming application in mobile version which acts as client, so that existing system can act as server. In this research, the application is built in native android platform. To exchange data with the server, it is necessary to build a web service that is used as Application Programming Interface (API). The results of the development of android-based applications obtained 19 main features, while the results of web service development obtained 8 new classes on the system-based website. Unit testing is done using white-box method and validation testing is done by black-box method. The results of unit testing and validation testing yield a 100% value, which means all features work in accordance with requirements.